PROSES DESORPSI GAS KHLOR DALAM LARUTAN SODIUM HYPOKHLORIT DENGAN MENGGUNAKAN REAKTOR TRICKLE BED - Isna Syauqiah (Universitas Lambung Mangkurat, 2005)
Chlorine elimination from aqueous solution by desorption process in trickle bed reactor was investigated. The object of this research is to study the chlorine desorption process from aqueous solution that containing free chlorine using a trickle bed reactor packed with rasching ring. The experiment conducted in the trickle bed reactor with the following specification : glass column with 4.6 cm diameter and 35 cm length; raschig ring packing 0.3 cm diameter and 0.85 cm length. The solution aqueous containing free chlorine is made from dissolving a certain quantity of sodium hypochlorit (NaOCl) in water with addition of hydrochloric acid (HCl). The operating conditions of experiment are : room temperature, atmospheric pressure and initial concentration of NaOCl = 0,1%, and the experiment varibles are : pH of solution (1 – 5) ; gas flow rate (232 ml/s – 85 ml/s). The result of experiment shows that the chlorine concentration decrease significantly with decreasing pH. However, it’s slygtly influence by the gas flow rate.